Computerized planimetry to assess clinical responsiveness in a phase II randomized trial of topical R333 for discoid lupus erythematosus. (17th April 2018) - Presto, J.K.; Okon, L.G.; Feng, R.; Wallace, D.J.; Furie, R.; Fiorentino, D.; Werth, V.P.
Summary: Background: R333 is a topical janus kinase and spleen tyrosine kinase inhibitor being evaluated for discoid lupus erythematosus (DLE) treatment. There is no validated measure to assess the area of active DLE lesions. Objectives: To evaluate R333 efficacy and assess a technique to measure responsiveness. Methods: Fifty‐four patients with DLE were randomized in a double‐blind design to R333 or placebo. Primary end point was the proportion of patients achieving ≥ 50% decrease in erythema and scale based on lesional Cutaneous Lupus Erythematosus Disease Area and Severity Index TM for all treated lesions at week 4. Two‐dimensional (2D) area measurements for each lesion were recorded at baseline and weeks 1–6. Eighty‐eight photographs (44 pre‐ and 44 post‐treatment) were obtained from the trial and change in size of active areas was analysed by computerized planimetry and physician‐assessed area change (PAAC). Results: Thirty‐six patients were randomized to R333 and 18 patients were randomized to placebo. Primary end point was not achieved. There was a strong association between lesion activity and physician global assessment ( P < 0·001). Photos of 42 patients assessed by computerized planimetry demonstrated excellent inter‐ and intra‐rater reliability. Area change by computerized planimetry showed a strong correlation with PAAC (Spearman r = 0·72). Area change by 2D measurements showed a weak correlation with PAAC (Spearman r = 0·29). Conclusions: Four weeks of R333 treatment did not result in significant improvement in lesion activity. Lesion activity and area change using computerized planimetry are better determinants of responsiveness than area change using 2D measurements. Abstract : What's already known about this topic? Topical janus kinase (JAK)/spleen tyrosine kinase (Syk) inhibitors may be useful in the treatment of discoid lupus erythematosus (DLE) lesions. Validated outcome measures are critical in that they enable the objective evaluation of disease for clinical practice, therapeutic trials and translational research. There is a need to validate an approach that can evaluate individual cutaneous lesions to assess the effects of topical therapies in DLE. What does this study add? The topical JAK/Syk inhibitor R333 did not result in clinical improvement of DLE lesions after 4 weeks of treatment. Computerized planimetry is a reliable technique for measuring the area of DLE lesions. Lesion activity and area determined by computerized planimetry are better able to assess clinical responsiveness to topical medication for DLE lesions than the area determined using two‐dimensional measurements. Plain language summary available online Respond to this article